PENYUSUNAN KURIKULUM OPERASIONAL PADA SATUAN PAUD BERBASIS KURIKULUM MERDEKA - Rachma Hasibuan; Ruqoyyah Fitri; Irena Y Maureen; Ajeng Putri Pratiwi (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
Curriculum is dynamic and it needed to change to adjust to the context and goals of the society, however it is also not always easy for teachers who implement the curriculum. This community service activity aims to help PAUD teachers, especially Kindergarten (TK) levels in understanding the existence of curriculum changes, namely the Kurikulum Merdeka so that teachers can understand, plan, and implement learning at the kindergarten level. The target of this community service (PKM) activity is 25 kindergarten teachers in Mojokerto City. The PKM design carried out were: socialization of the independent curriculum and training in preparing activity plans in learning in kindergarten. This community service uses the lecture, discussion, assignment, and simulation methods, this PKM is carried out both online and offline to provide experience in compiling and implementing learning in kindergarten. The results of this PKM can be seen from the results of the pre-test and post-test. Kindergarten teachers in the City of Mojokerto already have knowledge of the Independent Curriculum but not in its entirety. Based on the results of a questionnaire filled out by 25 kindergarten teachers in Mojokerto City, it was found that only 8.7% of institutions had used the Kurikulum Merdeka. 52.2% use a mixed curriculum (50% PAUD 2013 Curriculum and 50% Kurikulum Merdeka). As many as 39.1% still use the 2013 PAUD Curriculum, so it can be concluded from this PKM is the creation of the ability of kindergarten teachers in preparing, planning and implementing Kurikulum merdeka appropriately.